2019
DOI: 10.7150/ijms.35158
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 and MLRs: A potential target for neuronal growth and neuroplasticity after ischemic stroke

Abstract: Ischemic stroke is a leading cause of morbidity and mortality worldwide. Thrombolytic therapy, the only established treatment to reduce the neurological deficits caused by ischemic stroke, is limited by time window and potential complications. Therefore, it is necessary to develop new therapeutic strategies to improve neuronal growth and neurological function following ischemic stroke. Membrane lipid rafts (MLRs) are crucial structures for neuron survival and growth signaling pathways. Caveolin-1 (Cav-1), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 173 publications
0
9
0
Order By: Relevance
“…Caveolin-1 is a cholesterol binding protein important for neuronal survival and growth [ 170 ]. In this connection, drugs that upregulate caveolin-1 have been reported to promote neuronal plasticity and growth via PI3K and GSK3β signaling [ 171 ]. In recent times, the role of fatty acid binding protein 4 isoform (FABP 4 ] has also been envisaged in ischemic stroke.…”
Section: Novel Exploratory Targets In Ischemic Strokementioning
confidence: 99%
“…Caveolin-1 is a cholesterol binding protein important for neuronal survival and growth [ 170 ]. In this connection, drugs that upregulate caveolin-1 have been reported to promote neuronal plasticity and growth via PI3K and GSK3β signaling [ 171 ]. In recent times, the role of fatty acid binding protein 4 isoform (FABP 4 ] has also been envisaged in ischemic stroke.…”
Section: Novel Exploratory Targets In Ischemic Strokementioning
confidence: 99%
“…Also involved in neurogenesis, lncRNA Gm15577 was identified in the Nbs1-deficient mouse model. Yue et al [ 80 ] demonstrated that Gm15577 regulates the RNA expression of Shh, Nerg1, and β-catenin, and has important functions in neuronal growth and neuroplasticity [ 81 ].…”
Section: Lncrnas and Pathways Involved In Non-syndromic Intellectumentioning
confidence: 99%
“…Cav1 regulates neuronal signaling [ 27 ]. When upregulated or overexpressed in the brain, Cav1 enhances receptor function and neuronal plasticity [ 28 , 29 , 30 ]. For example, enhancing Cav1 in the brain is indicated to be a potential therapy for enhancing neuroplasticity after neurodegeneration, cerebral ischemia and stroke [ 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…When upregulated or overexpressed in the brain, Cav1 enhances receptor function and neuronal plasticity [ 28 , 29 , 30 ]. For example, enhancing Cav1 in the brain is indicated to be a potential therapy for enhancing neuroplasticity after neurodegeneration, cerebral ischemia and stroke [ 29 , 31 ]. Conversely, Cav1 overexpression in non-neuronal cells has been shown to mediate tumorigenesis and enhance oxidative stress in cancer [ 32 ].…”
Section: Introductionmentioning
confidence: 99%